Tanggung Jawab Nahkoda pada Kecelakaan Kapal Dalam Pengangkutan Penumpang dan Barang Melalui Laut di Indonesia - Herman Susetyo (Faculty of Law, Universitas Diponegoro, 2010)
Carriage by sea is one of the oldest mode of transportation in the world, which is used to transport people and goods. During the transportation process from the loading port to destination port, the safety of passengers and cargo is the responsibility of the captain as the leader of the ship. Navigation facilities in the cruise was more modern, the safety of shipping arrangements are always adjusted to the prevailing international conditions, but still often ship accidents in Indonesia has become one indication of the lack of regulations on the responsibiliy of the ship's captain in the event of an accident and causes damages to he passengers and owners of cargo. Undang-undang No. 17 Tahun 2008 tentang Pelayaran which replaces Undang-undang No. 21 Tahun 1992 is expected to reduce the occurrence of a ship accident, because the shipping law have set criminal sanctions for the ship's captain whi reglect or fault causing harm/death during the shipping